Kemampuan Berpikir Aljabar Siswa SMP dalam Menyelesaikan Masalah Matematika Ditinjau dari Gaya Kognitif Adaptasi dan Inovasi - Puspita, Dhea Berliana; Kurniasari, Ika (Universitas Negeri Surabaya, 2025)
Algebraic thinking ability is an individual's ability to implement six types of mathematical thinking abilities, namely generalization, abstraction, analytical thinking, dynamic thinking, modeling, and organization. Algebraic thinking ability has a close relationship with problem-solving and cognitive style. This study aims to describe the algebraic thinking ability of junior high school students with cognitive style adaptation and innovation in solving math problems. This research used a descriptive qualitative approach. The research subjects selected were one student with an adaptation cognitive style and one with an innovation cognitive style, high mathematics ability, and the same gender. Researchers collected data using a cognitive style questionnaire, math ability, and problem-solving tests. The results showed that the ability of algebraic thinking of students with cognitive styles of adaptation and innovation in understanding the problem includes explaining the meaning of the problem with their language, identifying the problem by writing the information known and asked, and simplifying the information. In making plans, students can use abstract symbols, represent information coherently, tell pattern relationships mathematically, and find the pattern in question. In implementing the plan, students can use patterns to solve the problem, use intuitive methods, and identify the relationship between white and gray paving blocks. In re-examining, students review the steps of completion, ensure the correctness of the answer, and write conclusions. Students with cognitive styles of adaptation and innovation fulfill all indicators and show differences in working, but innovative students have not displayed a creative answer.